Efecto del programa social Haku Wiñay en el nivel de pobreza extrema rural en la unidad territorial de Iquitos 2016-2023 - Caritimari Saquiray, Jenifer Haydee (2025)
Growing socioeconomic inequality highlights the need to strengthen and optimize social programs like Foncodes’ Haku Wiñay to improve their effectiveness and target the most vulnerable households. In this context, this research posed the question: What is the effect of the Haku Wiñay social program on the level of rural extreme poverty in the Territorial Unit of Iquitos during the period 2016-2023? To answer this question, we analyzed semiannual records of public spending executed on the Haku Wiñay social program in the provinces of Maynas, Alto Amazonas, Datem del Marañón, Loreto, Mariscal Ramón Castilla, Putumayo, and Requena. We also studied socioeconomic indicators such as the level of extreme monetary poverty, the level of economic dependency, and the average income of the rural population in the aforementioned jurisdictions of the department of Loreto. The results of the econometric analysis suggest that the Haku Wiñay social program has significantly contributed to reducing extreme rural poverty in the Iquitos Territorial Unit during the 2016-2023 period, with a regression coefficient of β1=-4.18e-9. Empirical evidence indicates that an increase in the program's budget execution is associated with a decrease in the level of extreme rural poverty, highlighting its impact on improving the living conditions of vulnerable populations.